CONVERTING E-BOOK INTO AUDIOBOOK TO ENHANCE ENGLISH RECEPTIVE SKILL - Wibowo, J Ari (English Education:Journal of English Teaching and Research, 2016)
Recently, technology is getting common and cheap for people. It can be reached easily around them, even in their grasp. The development of smartphone and various free applications bring great opportunity and easiness in live and learning process as well. Their integration can be a potential media to improve learners’ English competence, especially their receptive skill. There are three free apps needed to change e-book into audiobook in the smartphone, consist of FBReader, FBReader TTS plugin and Ivona. A common writing in the e-book can be change into a voice which one can hear with or without read it. It is a new way to practice and improve listening and reading skill. Here, some potentials, advantages and also pedagogical implications of them are elaborated. It is expected that learners can improve their English skills while having fun. Keyword: FBreader, FBReader TTS plugin, Ivona, smartphone, receptive skill